Post-diagnosis adiposity, physical activity, sedentary behaviour, dietary factors, supplement use and colorectal cancer prognosis: Global Cancer Update Programme (CUP Global) summary of evidence grading - Tsilidis, Konstantinos K.; Markozannes, Georgios; Becerra-Tomás, Nerea; Cariolou, Margarita; Balducci, Katia; Vieira, Rita; Kiss, Sonia; Aune, Dagfinn; Greenwood, Darren C.; Dossus, Laure; González-Gil, Esther M.; Gunter, Marc J.; et al. (International journal of cancer, 2024)
Based on the World Cancer Research Fund Global Cancer Update Programme, we performed systematic reviews and meta-analyses to investigate the association of post-diagnosis adiposity, physical activity, sedentary behaviour, and dietary factors with colorectal cancer prognosis. We searched PubMed and Embase until 28th February, 2022. An independent expert committee and expert panel graded the quality of evidence. A total of 167 unique publications were reviewed, and all but five were observational studies. The quality of the evidence was graded conservatively due to the high risk of several biases. There was evidence of non-linearity in the associations between body mass index and colorectal cancer prognosis. The associations appeared reverse J-shaped, and the quality of this evidence was graded as limited (likelihood of causality: limited-no conclusion). The evidence on recreational physical activity and lower risk of all-cause mortality (relative risk [RR] highest vs. lowest: 0.69, 95% confidence interval [CI]: 0.62-0.77) and recurrence/disease-free survival (RR: 0.80, 95% CI: 0.70-0.92) was graded as limited-suggestive. There was limited-suggestive evidence for the associations between healthy dietary and/or lifestyle patterns (including diets that comprised plant-based foods), intake of whole grains and coffee with lower risk of all-cause mortality, and between unhealthy dietary patterns and intake of sugary drinks with higher risk of all-cause mortality. The evidence for other exposures on colorectal cancer outcomes was sparse and graded as limited-no conclusion. Analyses were conducted excluding cancer patients with metastases without substantial changes in the findings. Well-designed intervention and cohort studies are needed to support the development of lifestyle recommendations for colorectal cancer patients.
Gesehen am 03.04.2025